Akseptabilitas Orang Tua Terhadap Anak Berkebutuhan Khusus di Kota Yogyakarta (Studi Kasus Pada Lembaga Federasi Komunikasi Keluarga Penyandang Disabilitas) - Erlita Normasari; Meita Fitrianawati; Nurul Hidayati Rofiah (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the stages of acceptability, acceptability aspects, and acceptability factors of parents to children with special needs in the city of Yogyakarta.The subjects of this study were parents and families of children with special needs. Subject selection using purposive sampling. The object of the research is the acceptability of parents who have special needs and are members of the Federation of Family Communities with Disabilities (FKKPD). This research is a qualitative research with collection techniques through interviews and documentation, data credibility test using reference materials, and interactive model data analysis techniques (data collection, data reduction, data presentation, and drawing conclusions).The results showed that parents had reached the stage of acceptability (accepting) their children with special needs, by going through several stages of denial (denial), anger (anger), bargaining (bargaining), depression (depression) and acceptance (acceptance). This can be seen from the acceptance aspects and is supported by the acceptance factors of parents. However, there is one parent who does not accept their child with special needs.